Modelo de referência para estruturar o programa de qualidade seis sigma: proposta e avaliação - Santos, Adriana Barbosa (2006)
With the growth of customer demand level, at last two decades it appeared quality improvement approach focusing customer satisfaction as the way to the organizations improve the efficiency and effectiveness of their processes. Though this, to get their aim, it was necessary broke some paradigms; to stimulate creativity; to innovate; to intensify the effort to reduce processes variation; and above all to assume customer satisfaction in all operations as a priority. Six Sigma approach has been solidifying as an efficient alternative to organizational growth on the strength of quality levels elevation. But, how can we define Six Sigma? Making a theoretical and conceptual research several definitions founded in literature were rescued and examined with purpose to compose a broader definition which translates better Six Sigma meaning. About structure of Six Sigma Quality Program (PQSS), this thesis became as a link between theory and practice when it aided others theories to Six Sigma context and when it used empirical subsidies to identify and evaluate the essential components to structure the PQSS. The empirical subsidies were obtained from qualitative research (case studies) involving four Brazilian subsidiaries of American multinational companies. After to analyze the empirical evidences, it was possible to formalize a set of arguments to purpose a Reference Model to structure the PQSS. This model is sustained by the followings components: strategic orientation; statistical thinking; performance measurement; Six Sigma methodology; and people graduation and qualification. To evaluate the Reference Model it was developed a quantitative research based in Green belts, Black belts and Master Black belts information. Statistical results showed that each one of these components has a meaningful relevance to compose the minimal structure to the PQSS. As principal conclusions this thesis highlights: (1) the PQSS as an integrator program of strategic and operational objectives; (2) strategic orientation and alignment are fundamental to define Six Sigma projects; (3) the use of performance measures increases the potential of Six Sigma projects; (4) its not clear for many specialists that statistical thinking is a background to PQSS; (5) Six Sigma projects are catalysts of a system which uses these projects to reflect it strategic orientation and customer focus importance to get measurable results; and (6) the Reference Model can be valid and can be utilized to structure or re-structure the PQSS implementation.